Analisis Kebijakan Pendidikan dalam Masa Darurat Penyebaran Covid-19 (Analisisis SE Mendikbud No.4 tahun 2020) - Marlina, Leni; Bashori, Bashori (Institut Agama Islam Negeri Lhokseumawe, 2021)
The Covid-19 pandemic has changed many aspects of life, one of which is education. The transformation and acceleration of education is a challenge that must be faced by the government and educational institutions. This article aims to find out how education policies during the COVID-19 pandemic are in accordance with Circular No. 4 of 2020 concerning the Implementation of Education Policies in the Emergency Period for the Spread of Coronavirus Disease (covid-19) and various teaching media that can be used to support online teaching and learning activities. /on line. This study uses relevant literature review research methods and surveys of students and teachers in one school using a google form which is processed and interpreted as a result. The data taken in this study came from various sources and research results related to the investigated case, then the data was processed using qualitative descriptive analysis techniques, which is a way of processing data that is formulated in the form of words or sentences and data collection techniques using observation techniques. , interviews and documentation. Based on research, various teaching media are used such as youtube, educational platforms such as whatsapp, google classroom, google meet, zoom cloud meeting, the teacherscorner. net and others. The results of this study indicate that the use of teaching media and educational platforms may be an alternative solution in learning, for the sake of continuity of learning in every educational unit during the Covid-19 Pandemic.